The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1992
DOI: 10.1002/hep.1840150319
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and hemodynamic responses of bivascularly perfused rat liver to nerve stimulation, noradrenaline, acetylcholine and glucagon in thioacetamide-induced micronodular cirrhosis

Abstract: Thioacetamide-induced rat cirrhosis was characterized by single-cell necroses, fibrosis, nodular parenchyma, decrease in parenchymal volume density and an increase in liver weight per body weight so that the total amount of parenchyma was not altered. The glycogen content was normal, and signs of decompensation were not found. Isolated livers were single-pass perfused by way of both the hepatic artery and the portal vein. In the normal livers stimulation of the nerve plexuses around the hepatic artery or porta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

1993
1993
2013
2013

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 35 publications
(19 reference statements)
1
3
0
1
Order By: Relevance
“…More recently, Rockey and Chung9 have reported a 75% decrease in cNOS activity by the citrulline assay in isolated sinusoidal endothelial cells from a rat model of carbon tetrachloride induced cirrhosis. Depletion of constitutively expressed NO in the cirrhotic liver is consistent with the finding that the intrahepatic portal vascular bed of the cirrhotic liver exhibits hyper-reactivity to vasoconstriction by noradrenaline20and to sympathetic nerve stimulation,21 in contrast to the hyporesponsiveness to vasoconstrictor agents known to occur in other regions of the peripheral vasculature in cirrhosis 222.…”
Section: Discussionsupporting
confidence: 82%
“…More recently, Rockey and Chung9 have reported a 75% decrease in cNOS activity by the citrulline assay in isolated sinusoidal endothelial cells from a rat model of carbon tetrachloride induced cirrhosis. Depletion of constitutively expressed NO in the cirrhotic liver is consistent with the finding that the intrahepatic portal vascular bed of the cirrhotic liver exhibits hyper-reactivity to vasoconstriction by noradrenaline20and to sympathetic nerve stimulation,21 in contrast to the hyporesponsiveness to vasoconstrictor agents known to occur in other regions of the peripheral vasculature in cirrhosis 222.…”
Section: Discussionsupporting
confidence: 82%
“…We have studied a model for hepatic encephalopathy in mice with liver damage generated by bile duct ligation and TAA administration. TAA is a hepatotoxin that causes intrahepatic metabolic changes (40) and has often been used to induce cirrhosis in animals (41). Our previous studies have shown that cerebral dysfunction accompanies TAA-induced cirrhosis and may partly reflect the condition of hepatic encephalopathy (23).…”
Section: Discussionmentioning
confidence: 99%
“…Also, the reduced generation of the oxygen radical may have been caused by the lowered energy charge (37). On the other hand, alterations of the membrane structure reported in cirrhosis (38,39) may have affected the formation of the multimolecular oxidase complex. It is interesting to note that the lowered membrane fluidity in chemically-induced cirrhosis changed the activity of enzymes embedded in the membrane (39).…”
Section: Discussionmentioning
confidence: 99%